The Compatibilization Effects of Alkylated-grafted-Graphene Oxide on Polypropylene/Polystyrene Blends - Yanping Hao; Xin Zhao; Jie Dong; Qinghua Zhang (International Journal of Polymer Science)
Modified graphene oxide (GO) was synthesized by covalently grafted alkylated chains on GO sheets and their compatibilization effects on the morphologies and mechanical properties of immiscible polypropylene/polystyrene (PP/PS) blends were investigated. Alkylated-grafted-GO/PP/PS batches were fabricated by melt-mixing approach and displayed different morphologies with various modified GO loadings. When the content of alkylated-grafted-GO is 0.2 wt%, the tensile strength of obtained composite could reach 17.97 MPa, showing a 36.3% enhancement compared to that of pristine PP/PS, indicating the positive compatibilization of modified GO in polymer blends. Moreover, the mixing order also plays an important role in achieving the desired improvement in properties. Due to the preferential location of modified GO in PP phase, a favorable “transition zone” could be formed at the interfacial region of two polymers when alkylated-grafted-GO was premixed with PS and subsequently mixed with PP, leading to an improvement of compatibilization between two polymers and an enhancement of mechanical properties. However, serious phase separation and declined tensile strength were obtained with a reversed mixing sequence.